Parents' motivations that contribute to homeschool practices - Loh Su Ling (2013)
The purpose of this study to investigate the motivations for parents to homeschool their children and to explore how parents' motivations regulate their behaviour that lead to the children learning regulations. This phenomenological study involved parents from four local homeschool families. Their experiences on homeschool were described and interpreted through interviews, observations and document review. Parents decided to homeschool their children due to the difference in between their perception on learning in school and their own learning conception. Their belief on the conception of learning, character building, family values and a great sense of responsibility serve as well-internalized extrinsic motivation that regulate their behaviour in terms of parenting style and persistence. The parents seemed to assume the role of autonomy - supportive and provide structure in homeschooling their children which in turn help to regulate the learning behavior of their children. The children regulate their learning through personal goal setting, self-assessment and adaptive help-seeking.